Pyridoxine, but not thiamin, improves growth performance of weanling pigs - J C Woodworth; R E Musser; J A Loughmiller; S A Moser; G S Grinstead; P R O'Quinn; Robert D Goodband; Jim L Nelssen; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1997)
Two trials were conducted to determine whether pyridoxine or thiamine needs to be added to the diet for weanling pigs. In the first trial, weanling pigs were fed either a control diet or diets containing added thiamin (2.5 or 5.0 g/ton) or pyridoxine (3.5 or 7.0 g/ton). From d 0 to 14 after weaning, pigs fed added pyridoxine had increased ADG and ADFI, with pigs fed 3.5 g/ton of added pyridoxine having the greatest response. Growth performance was not improved by added thiamin. In a second trial, weanling pigs were fed a control diet or diets containing 1, 2, 3, 4, or 5 g/ton added pyridoxine. From d 0 to 14 after weaning, increasing pyridoxine increased ADG and ADFI, with pigs fed 3 g/ton of added pyridoxine having the greatest ADG. Pyridoxine level had no influence on growth performance from d 14 to 35 after weaning. These results suggest that adding between 2 and 3 g/ton of pyridoxine to the diet maximizes ADG and ADFI from d 0 to 14 after weaning.; Swine Day, Manhattan, KS, November 20, 1997
Keywords: Swine day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 795; Swine; Weanling pigs; Growth; Pyridoxine; Thiamin